Digitalisasi Ekonomi : Peranan E-Commerce dalam Meningkatkan Daya Saing UMKM - Moh Hamzah; Adi Yasin Maulana Azis; Imam Khairuddin; Syafiul Anam; Zainul Qudsi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Digitalization of the economy is an important aspect to be integrated in the business world, especially UMKM, to improve their competitiveness. This qualitative study aims to reveal the importance of implementing technology in the small business sector so that it can grow. This research uses a qualitative method of literature study in which we review several previous studies. The results of this study show that the factors that can improve economic competitiveness are the utilization of technology such as implementing digital marketing that we can access through e-commerce, and technology training, as well as fostering self-awareness to love domestic products. Following up on the findings in this study, optimizing the application of technology in business activities is very important and must be encouraged, so that the small UMKM sector is not left behind and can compete with the business sector above it.